Eriophyoid mites (Acari: Prostigmata: Eriophyidae) associated with Compositae in Iran - Lotfollahi, Parisa; Irani-Nejad, Karim Haddad; Khanjani, Mohamad; Moghadam, Mohamad; de Lillo, Enrico (Zootaxa, 2013)
Five species of eriophyoid mites were identified during surveys of mite fauna associated with plant species of the family Compositae from Southwest of East Azerbaijan province during 2010 and 2011. Two of them, Aceria virgatae n. sp. from Centaurea virgata Lam. and Aceria xeranthemis n. sp. from Xeranthemum squarrosum Boiss., were found to be new to science. No damage symptoms were observed on their host plants. Aceria xeranthemis n. sp. is the first eriophyoid col-lected from the plant genus Xeranthemum. Aculops centaureae (Farkas, 1960) from Centaurea albonitens Turrill and Ace-ria cichorii Petanović et al. 2000 from Cichorium intybus L. are new records for Iranian mite fauna. The deutogyne female of Aceria anthocoptes (Nalepa) was recorded for the first time in Iran, too. A key to the species collected on Compositae in Iran is given.